Astragaloside-IV alleviates high glucose-induced ferroptosis in retinal pigment epithelial cells by disrupting the expression of miR-138-5p/Sirt1/Nrf2. Issue 4 (1st April 2022) - Tang, Xuyuan; Li, Xiuyi; Zhang, Dongyan; Han, Wei
ABSTRACT: Astragaloside-IV (AS-IV) (C41 H68 O14 ) is a high-purity natural product extracted from Astragalus, which has demonstrated biological activities. However, the effect of AS-IV on retinal pigment epithelial (RPE) cells in diabetic retinopathy (DR) remains unclear. In this study, high glucose (HG) was shown to promote ARPE-19 RPE cell death, increase the contents of reactive oxygen species (ROS) and oxidized glutathione (GSSG), and enhance lipid peroxidation density of mitochondrial membrane. In contrast, AS-IV decreased glutathione (GSH) content, mitochondria size and ridge. Addition of iron death inhibitor Ferrostatin-1 (Fer-1) to RPE cells decreased cell dead rate, thus indicating that HG-induced mitochondrial damage occurred due to ferroptosis. AS-IV alleviated HG-induced RPE cell damage. Furthermore, HG decreased levels of silent information regulator 1 (Sirt1) and nuclear factor (erythroid-derived 2)-like 2 (Nrf2) in the nucleus of RPE cells; AS-IV could alleviate these effects and increased expression of glutathione peroxidase 4 (GPX4), glutamate cysteine ligase (GCLM) and glutamate cysteine ligase catalytic subunit (GCLC), which are Nrf2 downstream genes. Mechanistically, AS-IV was shown to alleviate the effects of HG by increasing mir-138-5p expression in RPE cells and promoting expression of Sirt1 and Nrf2 in the nucleus. Transfection of mir-138-5p agonist inhibited the regulatory effects of AS-IV on Sirt1 and Nrf2, accompanied by decreased GPX4, GCLM and GCLC levels, and restoration of ferroptosis-related changes. Collectively, HG increased ferroptosis rate in RPE cells. In addition, AS-IV inhibited miR-138-5p expression, subsequently increasing Sirt1/Nrf2 activity and cellular antioxidant capacity to alleviate ferroptosis, resulting decreased cell death, which potentially inhibits the DR pathological process. Graphical abstract: uf0001